Implementation of Performance Measurement with BSC and MBNQA Integration System in RSUD dr. Soedomo Trenggalek - Lilik Absari (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The purpose of this study is to implement a performance measurement system with integration of Balanced Scorecard (BSC) and Malcolm Baldrige National Quality Award (MBNQA) at RSUD dr. Soedomo Trenggalek. With this integration model, it is expected to produce a comprehensive performance measurement system, so that it can measure all activities in the organization. Integration is done by mapping each BSC perspective, then the MBNQA perspective is disseminated into the BSC strategy map. Performance measurement results with the integration of BSC and MBNQA in RSUD dr. Soedomo Trenggalek as a whole is quite good, but there are still indicators that do not reach the standard. By doing performance measurement with the integration of BSC and MBNQA, it will measure all the performance of all organizational activities. The purpose of this study is to implement a performance measurement system with integration of the Balanced Scorecard (BSC) and Malcolm Baldrige National Quality Award (MBNQA) at the dr. Soedomo Trenggalek. With this integration model, it is expected to produce a comprehensive performance measurement system, so that it can measure all activities in the organization. Integration is done by mapping each BSC perspective, then the MBNQA perspective is disseminated into BSC strategy map. Research methods using case studies to understand in depth the performance of RSUD dr. Soedomo Trenggalek. With the implementation of a performance measurement system with integration of BSC and MBNQA in RSUD dr. Soedomo Trenggalek will produce a more comprehensive performance indicator, so that all organizational activities can be measured. Performance measurement results with integration of BSC and MBNQA in RSUD dr. Soedomo Trenggalek showed that performance was quite good, although there were indicators that had not reached the standard, especially on indicators of employee motivation, BTO, GDR and CRR. The indicator needs an increase to produce a better overall performance.